Investigating Light Hydrocarbon Pipeline Leaks: A Comprehensive Study on Diffusion Patterns and Energy Safety Implications - Shuxin Zhang; Xiaohui Xia; Yufa Deng; Xiaochun Han; Banghui Deng; Huituan Liu; Xi Yan; Liqiong Chen (Energies, 2025)
Light hydrocarbon fuels are widely utilized in industrial production and transportation due to their high calorific value and clean combustion characteristics. Compared to traditional oil tanker transportation, pipelines not only reduce transportation costs but also minimize environmental impact. To understand the leakage and diffusion law of light hydrocarbon pipelines, this paper takes light hydrocarbon pipelines as the research object, establishes the conceptual model of the process of light hydrocarbon leakage and diffusion, divides the four major processes of leakage and diffusion, analyzes the relevant theory, and deduces a formula. The numerical model of pipeline–air–soil leakage and diffusion was established to analyze the whole process of light hydrocarbon leakage and diffusion. The diffusion behavior of individual hydrocarbon components is examined, along with a comparative analysis between multi-component and single-component leakage scenarios. Simulation results reveal that the leakage process comprises three stages: an initial rapid diffusion phase, a transitional phase where a stable region begins to form, and a final stage where the diffusion pattern stabilizes around 800 s. C3 and C5 exhibit the largest diffusion ranges among gaseous and liquid hydrocarbons, respectively. In multi-component systems, the vaporization sequence suppresses the overall diffusion range compared to single-component cases, though gas-phase hydrocarbons tend to accumulate near the leakage source. Understanding the leakage and diffusion behavior of light hydrocarbon pipelines is crucial for energy security. By accurately modeling these processes, we can determine the impact zones of potential pipeline failures and establish appropriate safety buffers. This proactive approach not only safeguards human life and the environment but also ensures the reliable and uninterrupted delivery of energy resources. Consequently, such research is instrumental in fortifying the resilience and dependability of energy infrastructure.